Chronic Lung Disease in Canadian Aboriginal Children Is Not Caused by Abnormal Cilia - Bruce K Rubin; Vijay Kumar (Canadian Respiratory Journal)
BACKGROUND: It has been suggested that abnormalities of the airway cilia are responsible for some of the increased prevalence of bronchiectasis among the Polynesian population of New Zealand.